Effect of Spice Mixtures on Performance and Economics of Broiler Chicken: - D. Tewari; Chakara, Sonu Kumar (Indian Journal of Animal Nutrition, 2023)
To investigate the effect of spice mixture (turmeric, fenugreek, cinnamon, cumin and ajwain) on the performance and economics 250 broiler chicks (Vencobb-400Y) were randomly distributed into five dietary treatment groups- basal diet without supplement (NCG) or with antibiotic (PCG), spice mixture at 0.5% (SMG-0.5), spice mixture at 1.0% (SMG-1.0) and spice mixture at 1.5% (SMG-1.5) levels for five week. The effect of spice mixture on body weight gain, feed intake, feed conversion ratio, production indices and economics was assessed. After five weeks experiment, body weight gain in all SMG groups as well as PCG group had significantly (P